AK-47 : - Kahaner, Larry (Wiley, 2007)
Journalist Kahaner (The Quotations of Chairman Greenspan: Words from the Man Who Can Shake the World) presents a detailed study of the AK-47, the single most deadly weapon ever produced, and its designer. Mikhail Kalashnikov, a mechanically inclined Russian soldier, came up with this simple submachine gun to counter superior German weaponry during World War II. Brought into mass production in 1947 (this date formed the final part of the weapon's name, Avtomat Kalashnikov 1947), the AK-47 was shipped by the Soviet Union to Eastern Europe, Africa, Asia, South America, and the Middle East during the Cold War. In part because they are so easy to make, 80 to 100 million AKs have been manufactured and distributed during the last 59 years. Moreover, the AK has proven a superior weapon to the American M-16. Kahaner provides an interesting discussion of how internal politics in the U.S. Army led it to adopt, instead, an inferior, lightweight machine gun. Kalashnikov, who lives in Russia today, never became rich from his design, but he did receive recognition outside his homeland for the impact of his weapon. A fascinating examination; recommended for all libraries.